Removal of Oil From Wastewater Using Walnut-Shell - Ismail, Dr. Zainab Ziad (Al-Khwarizmi Engineering Journal, 2017)
The ability of pulverized walnut-shell to remove oil from aqueous solutions has been studied. It involves two-phase process which consists of using walnut-shell as a filtering bed for the accumulation and adsorption of oil onto its surface. Up to 96% oil removal from synthetic wastewater samples was achieved while tests results showed that 75% of oil can be removed from the actual wastewater discharged from Al- Duara refinery in the south of Baghdad.